An updated review on solar air heating systems. (October 2022) - Almutairi, Khalid; Almutairi, Mubarak; Harb, Kamal; Marey, Omar; Aungkulanon, Pasura
Abstract: Solar energy is one of the most attractive types of renewable sources with applicability for heating in different scales. Several technologies can be employed for air heating by using solar radiations. The performance of the solar heating systems is dependent on different elements including the type of technology, configuration and operating conditions. In the present work, different solar air heating systems and the factors affecting their performance are reviewed and discussed with focus on the recently published studies in order to cover the contents that have not been considered in the previous review articles. Furthermore, the studies considered potentials of solar energy to be integrated with other renewables to drive air heating systems are included here and reviewed. According to the findings it can be summarized that efficient air heating systems utilizing solar energy can be applied for different purposes especially thermal comfort in buildings. The performance of these systems can be improved by several approaches such as modifications on the absorber plate, using proper operation mode, and optimization of the system. Furthermore, adding some components such as storage unit, heat recovery system and turbulator would be beneficial in term of efficiency.